Dekret Demofantosa – ateńskie prawo przeciw tyranii - Rominkiewicz, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article is devoted to one of the Athenian laws against tyranny — the decree of Demophantos. It was aimed at protecting Athenian democracy against being overthrown again, and thus at preventing any authoritarian form of rule in this polis in the future. The author presents his own translation of this law, cited in Andokides’s speech On the Mysteries (1.96–98). Moreover, he supports the view of M. Canevaro and E.M. Harris, according to which the text of the decree cannot be perceived as an authentic document, being in fact a later addition to this speech. The only elements of the decree that can be regarded as genuine are those, which are confirmed in speeches of Demostenes (Against Leptines 159–162) and Lycurgus (Against Leocrates 124–127).
Keywords: tyrania; tyran; oligarchia; ateńskie prawa przeciw tyranii; dekret Demofantosa